PENGUJIAN SEDIAAN SAMPO ANTI KETOMBE DARI EKSTRAK DAUN KETEPENG CINA (Cassia alata L.) DAN SARI BUAHJERUK NIPIS (Citrus aurantifolia S.) SEBAGAI ANTI JAMUR Pityrosporum ovale - Siska Aditiani; Rizki Amelia Nasution; Irda Nila Selvia (BIOMA : JURNAL BIOLOGI MAKASSAR, 2025)
Dandruff is a scalp condition caused by the fungus Pityrosporum ovale. The use of natural components as active ingredients in anti-dandruff shampoo preparations, such as Chinese longan leaves (Cassia alata L.) and lime (Citrus aurantifolia S.), provides a safer alternative to chemicals that may harm the skin. The purpose of this study is to assess the antifungal activity of a combination of Chinese ketepeng leaf extract (Cassia alata L.) and lime juice (Citrus aurantifolia S.) against Pityrosporum ovale, as well as to determine the optimal concentration of Chinese ketepeng leaf extract and lime juice that inhibits the growth of the Pityrosporum ovale fungus. The research was conducted using an experimental method with a quantitative approach. This study began with testing the activity of lime fruit extracts and juice with concentrations of 10%, 15%, 20%, 25%, and 30%, but obtained the best results for testing shampo preparations based on Pharmacopoeia IV, namely at concentrations of 20% and 25%, and two supporting controls, namely control (-) without extracts and juice and control (+) which is clear shampoo. The study found that the inhibition zone on Pityrosporum ovale fungi was 10.16 mm in the control (-), 16.36 mm at the 20% concentration, 20.10 mm at the 25% concentration, and 20.30 mm in the (+) control. Chinese ketepeng leaf extract and lime juice can work well as an alternative ingredient in natural anti-dandruff shampoo formulations. The results of the preparation evaluation revealed that the formula with a concentration of 20% met the characteristics of a good shampoo according to Pharmacopoeia IV.